2008
DOI: 10.1021/bm700797b
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Multilayer Arrays of Viral Nanoparticles via Biospecific Recognition: A Quartz Crystal Microbalance with Dissipation Monitoring Study

Abstract: The development of multilayered thin film assemblies containing (bio)molecules is driven by the need to miniaturize sensors, reactors, and biochips. Viral nanoparticles (VNPs) have become popular nanobuilding blocks for material fabrication, and our research has focused on the well-characterized plant virus Cowpea mosaic virus (CPMV). In a previous study, we have reported the construction of multilayer VNP assemblies. Here we extend these studies by providing further details on the formation and properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 42 publications
3
52
1
Order By: Relevance
“…Grafting was again mediated by a biotin tag. A linker of about 3 nm in contour length (47) was placed between the biotin and the reducing end of HA to enhance the conformational freedom of the surface-bound oHA chains. Each oHA chain is 4.5 nm long and can interact with only one TSG-6 molecule at a time, and previous studies have shown that ϳ5 sugar monomers probably fill its HA-binding site (48).…”
Section: Design Of Ha Model Films To Study Tsg-6-hyaluronanmentioning
confidence: 99%
“…Grafting was again mediated by a biotin tag. A linker of about 3 nm in contour length (47) was placed between the biotin and the reducing end of HA to enhance the conformational freedom of the surface-bound oHA chains. Each oHA chain is 4.5 nm long and can interact with only one TSG-6 molecule at a time, and previous studies have shown that ϳ5 sugar monomers probably fill its HA-binding site (48).…”
Section: Design Of Ha Model Films To Study Tsg-6-hyaluronanmentioning
confidence: 99%
“…9). To study the properties of the multilayers, CPMV LbL assembly was followed in real time and in situ using quartz crystal microbalance with dissipation monitoring (QCMD; Steinmetz et al 2008a). In particular, the effect of modifying the density of biotin molecules attached via longer and shorter linkers to the virus surface was investigated.…”
Section: Cowpea Mosaic Virusmentioning
confidence: 99%
“…The merged images confirmed that the virions sat one on top of the other; this is in contrast with a mixed-layer monolayer, where the images do not line up, as the particles are occupying the same layer and competing for binding sites. QCMD (quartz crystal microbalance with dissipation monitoring) studies of the alternating deposition of biotin-modified CPMV, with different biotin-spacer length, and SAv on a biotinylated solid-supported lipid bilayer showed that the level of biotin coverage and the length of the biotin spacer affect the degree of intra-and inter-layer cross-linking [15]. A long spacer and high biotin coverage gave the most regular and densest arrays; the degree of layer coverage and of cross-linking can therefore be highly tuned.…”
Section: Layer and Array Formationmentioning
confidence: 99%